2018
DOI: 10.1016/j.envpol.2017.09.086
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric nitrogen deposition in the Yangtze River basin: Spatial pattern and source attribution

Abstract: The Yangtze River basin is one of the world's hotspots for nitrogen (N) deposition and likely plays an important role in China's riverine N output. Here we constructed a basin-scale total dissolved inorganic N (DIN) deposition (bulk plus dry) pattern based on published data at 100 observational sites between 2000 and 2014, and assessed the relative contributions of different reactive N (N) emission sectors to total DIN deposition using the GEOS-Chem model. Our results show a significant spatial variation in to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(35 citation statements)
references
References 72 publications
3
32
0
Order By: Relevance
“…Ambient N addition plots received equal dose of water. This N deposition rate is higher than the current natural N deposition rate (ranging from 0.87 to 1.38 g N ha −1 year −1 ) in this region, but atmospheric N deposition rates as high as 5.46 g m −2 year −1 in China (Xu et al, ). A recent study in the same region demonstrated that N addition rate of 8 g m −2 year −1 led to N saturation in soil (Peng & Yang, ).…”
Section: Methodsmentioning
confidence: 82%
“…Ambient N addition plots received equal dose of water. This N deposition rate is higher than the current natural N deposition rate (ranging from 0.87 to 1.38 g N ha −1 year −1 ) in this region, but atmospheric N deposition rates as high as 5.46 g m −2 year −1 in China (Xu et al, ). A recent study in the same region demonstrated that N addition rate of 8 g m −2 year −1 led to N saturation in soil (Peng & Yang, ).…”
Section: Methodsmentioning
confidence: 82%
“…It plays an important role in formation of (NH 4 ) 2 SO 4 and NH 4 NO 3 aerosols (Seinfeld and Pandis, 2006). These secondary inorganic aerosols account for 40-57 % of the PM 2.5 concentrations in eastern China (Yang et al, 2011;Huang et al, 2014). Based on monthly mean molar concentrations, there were significant positive linear correlations between W. Xu et al: Spatial-temporal patterns of inorganic nitrogen air concentrations NH 3 and pNH + 4 , NO 2 and pNO − 3 , SO 2 and pSO 2− 4 , pNH + 4 and pNO − 3 , and pNH + 4 and pSO 2− 4 at all land use land types except for a non-significant relationship of NH 3 with pNH + 4 at background sites ( Fig.…”
Section: The Role Of Nh 3 In Mitigation Of N R Air Pollutionmentioning
confidence: 99%
“…Increasing N deposition may be favorable to C sequestration in subtropical forests [23]. Atmospheric wet N deposition on the western edge of the Sichuan Basin (known as the "rainy zone of west China") is much higher than the mean value across China, as a result of rich rainfall and reactive N [24]. Previous studies have indicated that extremely high N additions (100 and 150 kg N ha −1 yr −1 ) constrained the litter decomposition rate in subtropical forests [25][26][27].…”
Section: Introductionmentioning
confidence: 99%